PENGARUH KUALITAS PELAYANAN DAN RELATIONSHIP MARKETING TERHADAP LOYALITAS NASABAH DENGAN KEPUASAN NASABAH SEBAGAI VARIABEL INTERVENING PADA BANK BKK CABANG DAWE - Nisa, Fika Durrotun; Arumsari, Nurul Rizka; Karatri, Rhealin Hening (Universitas Muria Kudus, 2024)
The main purpose of this study is to understand and examine the effect of service quality and marketing on customer loyalty at Bank BKK Dawe Branch by considering customer satisfaction as an intervening varable. The method used is through the spread of quesinaries distributed to 100 customers of Bank BKK Dawe Branch. The data obtained were analyzed with SEM using the AMOS 24 analysis tool. The findings of this study confirm the following: (1) Quality of service has a significant and positive effect on customer satisfaction, (2) relationship marketing also has a positive and positive effect on customer satisfaction, (3) quality of service contributes positively and significantly to customer loyalty, (4) relationshipsship marketing also had a positive and significant effect on customer loyalty, and (5) customer satisfaction had a positive and significant effect on customer loyalty